Analysis of the Nse3/MAGE-binding domain of the Nse4/EID family proteins - Guerineau, Marc; Kriz, Zdenek; Kozakova, Lucie; Bednarova, Katerina; Janos, Pavel; Palecek, Jan (PloS one, 2012)
BACKGROUND: The Nse1, Nse3 and Nse4 proteins form a tight sub-complex of the large SMC5-6 protein complex. hNSE3/MAGEG1, the mammalian ortholog of Nse3, is the founding member of the MAGE (melanoma-associated antigen) protein family and the Nse4 kleisin subunit is related to the EID (E1A-like inhibitor of differentiation) family of proteins. We have recently shown that human MAGE proteins can interact with NSE4/EID proteins through their characteristic conserved hydrophobic pocket. METHODOLOGY/PRINCIPAL FINDINGS: Using mutagenesis and protein-protein interaction analyses, we have identified a new Nse3/MAGE-binding domain (NMBD) of the Nse4/EID proteins. This short domain is located next to the Nse4 N-terminal kleisin motif and is conserved in all NSE4/EID proteins. The central amino acid residues of the human NSE4b/EID3 domain were essential for its binding to hNSE3/MAGEG1 in yeast two-hybrid assays suggesting they form the core of the binding domain. PEPSCAN ELISA measurements of the MAGEC2 binding affinity to EID2 mutant peptides showed that similar core residues contribute to the EID2-MAGEC2 interaction. In addition, the N-terminal extension of the EID2 binding domain took part in the EID2-MAGEC2 interaction. Finally, docking and molecular dynamic simulations enabled us to generate a structure model for EID2-MAGEC2. Combination of our experimental data and the structure modeling showed how the core helical region of the NSE4/EID domain binds into the conserved pocket characteristic of the MAGE protein family. CONCLUSIONS/SIGNIFICANCE: We have identified a new Nse4/EID conserved domain and characterized its binding to Nse3/MAGE proteins. The conservation and binding of the interacting surfaces suggest tight co-evolution of both Nse4/EID and Nse3/MAGE protein families.
Keywords: Protein Binding; Chromosomal Proteins, Non-Histone; Recombinant Proteins; Schizosaccharomyces pombe Proteins; intracelulární signální peptidy a proteiny; inhibitor diferenciace 2; interakční proteinové domény a motivy; konzervovaná sekvence; techniky dvojhybridového systému; Computer Simulation; Conserved Sequence; molekulární sekvence - údaje; Amino Acid Sequence; mutageneze cílená; Intracellular Signaling Peptides and Proteins; jaderné proteiny; Amino Acid Substitution; molekulární modely; peptidové fragmenty; proteiny buněčného cyklu; rekombinantní proteiny; Schizosaccharomyces; vazba proteinů; Carrier Proteins; Models, Molecular; Mutagenesis, Site-Directed; Protein Interaction Domains and Motifs; Two-Hybrid System Techniques; lidé; Humans; substituce aminokyselin; sekvence aminokyselin; Schizosaccharomyces pombe - proteiny; chromozomální proteiny, nehistonové; počítačová simulace; Molecular Sequence Data; Inhibitor of Differentiation Protein 2; Peptide Fragments; Cell Cycle Proteins; Nuclear Proteins; transportní proteiny